Propitiating psychoeducational strategies for the teacher as counselor and promoter of mental health for children and youth. (Revista Venezolana de Salud Pública, 2018)
The objective of this research focused on the design of a psychoeducational program to promote the role of the teacher as a mentor and promoter of child and adolescent mental health Estadal Basic School "Julio Teodoro Arze" of the Conception Parish Barquisimeto, Lara State. Its main purpose was to contribute to the formation of human beings I integrate mental health, able to live harmoniously in society. It was based on theoretical research and theories that support the teacher's role as counselor and promoting mental health. Methodologically, this study was framed in the modality of feasible project, contentivo of the first three phases, supported by field research of a descriptive nature. With a population of 22 teachers who were applied an instrument that measured the need for training in their role as mentor and promoter of the mental health of the child and adolescent population; it was validated by expert opinion and its reliability was established by Alfha and Cronbach reliability coefficient Kuder - Richardson obtaining high reliability. Data were analyzed using descriptive statistics. The results showed the need for a psychoeducational program to promote the role of the teacher as a mentor and promoter of mental health. The other phases of the study determined the market feasibility, technical and financial as well as program design. Finally the conclusions that led response to the objectives and recommendations for the use of the program were developed.
Keywords: Mental health; counselor; promoter program